Implementation of Digital Marketing Ethics at CV. Yhave International Co. Ltd - Mariani Alimuddin; Ifah Finatry Latiep; Paramita Poddala (International Conference On Association Of Indonesian Entrepreneurship Study Programs, 2024)
This research examines the application of ethics in digital marketing at CV. Yhave International Co. Ltd, Makassar. The primary focus is on how ethics are implemented in digital marketing campaigns to address challenges and leverage opportunities. This study uses a qualitative approach with interview techniques, participatory observation, and document analysis. The results show that CV. Yhave is committed to transparency, personal data protection, social responsibility, and compliance with regulations. Steps taken include privacy policies, honest information disclosure, and support for relevant social issues. This research provides practical guidelines for other companies in managing their digital marketing ethics.